2014
DOI: 10.1002/adem.201400069
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Fibers Based on SiC and SiCN Systems: Current Research, Development, and Commercial Status

Abstract: Non-oxide ceramic fibers are of considerable interest due to the ability to combine the high performance, especially high temperature thermal and creep resistance, with the structural advantages of fibers including their use as reinforcements for metal (MMCs) and ceramic matrix composites (CMCs). In this paper the development of CVD SiC fibers and three generations of polymer derived SiC fibers over the past 50 years are discussed, illustrating the effect of fiber precursor and processing on the microstructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 100 publications
0
84
0
1
Order By: Relevance
“…Research activities in the eld of high performance nonoxide ceramic bers led, over the last 50 years, to the development of commercially available chemical vapour deposited (CVD) SiC monolaments [1][2][3] and three generations of SiC bers based on polymer derived ceramics (PDCs).…”
Section: Introductionmentioning
confidence: 99%
“…Research activities in the eld of high performance nonoxide ceramic bers led, over the last 50 years, to the development of commercially available chemical vapour deposited (CVD) SiC monolaments [1][2][3] and three generations of SiC bers based on polymer derived ceramics (PDCs).…”
Section: Introductionmentioning
confidence: 99%
“…The linear weight loss results from the high temperature instability of boria, given earlier by Reactions 6 -8 16 . The paralinear oxidation kinetics are characteristics of a non-protective oxide 11 creep resistance provided when the grain microstructure is fine, the Si: C ratio is stoichiometric, and the oxygen content is low 29 . A recent study by Wilson and Opila showed that commercially available Hi-Nicalon™ SiC fibers demonstrated Deal and Grove oxidation kinetics when exposed to dry oxygen environments 30 .…”
Section: Boron Nitride Oxidation Kineticsmentioning
confidence: 99%
“…This fiber, hereafter referred to as Sylramic, was reported by Lipowitz et al to be comprised of 95 wt% stoichiometric SiC, 3 wt% TiB2, 1.3 wt% B4C, 0.8 wt% O, and 0.7 wt% BN 34 . The fibers also contain free carbon 29,87 . The Sylramic fiber tow was supplied with a protective polyvinyl alcohol (PVA) sizing.…”
Section: Silicon Carbide Fibersmentioning
confidence: 99%
“…8) After that, many types of polymer-derived SiC fibers have been developed and commercialized. 3,4) These SiC fibers can show good mechanical strength and oxidation-resistance up to very high temperatures over 1000 o C. Of these SiC fibers, stoichiometric SiCpolycrystalline fibers (Tyranno SA, Hi-Nicalon Type S, and so on) have an excellent heat-resistance up to 2000 o C.…”
Section: -7)mentioning
confidence: 99%